CHINA'S MARITIME PIVOT: CPEC AND THE SOUTH CHINA SEA CONNECTION (Margalla Papers, 2024)
The China-Pakistan Economic Corridor (CPEC) is a critical component of China's Belt and Road Initiative (BRI), with far-reaching implications for regional and global geopolitics. This study investigates the strategic significance of CPEC in China's broader geopolitical strategy, particularly its South China Sea ambitions. The research question guiding this inquiry is: How does CPEC mitigate China's trade security vulnerabilities in the South China Sea region, and what are the implications for regional dynamics and global trade routes? By analysing the impact of CPEC on maritime security, energy trade, and regional power dynamics, this research reveals the corridor's pivotal role in enhancing China's energy security, countering US influence and Indian concerns, and solidifying China's position as a global economic powerhouse. The study also examines the challenges and opportunities arising from CPEC implementation, including its potential to reshape regional alliances and challenge existing global trade patterns. This research contributes to a deeper understanding of China's geopolitical ambitions and the significance of CPEC in advancing its strategic interests. Bibliography EntryAlla Ud Din, Shi Xiaolian and Uzma Siraj. 2024. "China's Maritime Pivot: CPEC and the South China Sea Connection." Margalla Papers 28 (2): 1-13.